2007
DOI: 10.1258/135763307780096203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the suitability of 'video-visits' for palliative home care: implications for practice

Abstract: We conducted a retrospective chart review to estimate the extent to which palliative home care visits could be carried out using videophones and to explore factors that might inform the eligibility criteria for video-visits. Four hundred palliative home care health records of deceased clients from 2002 were randomly selected from the Health Records Office in one Canadian health region. One visit was randomly selected from each of these health records. Three hundred and fifty-four visits were coded, and based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 5 publications
1
20
0
1
Order By: Relevance
“…Doolittle et al [16] carried out a retrospective chart review of 597 home visits to adult palliative care patients and identified that 65 percent of these visits could have been conducted by telehealth. Hebert et al [15] conducted a similar study, finding 43 percent of home visits could have received a ‘televisit’ instead. Demiris et al [25,35] criticised this form of evaluating suitability for a telehealth visit as a replacement for in person home visits in two papers, arguing that telehealth is not a suitable substitute for in person visits and that there were ethical implications to consider including the medicalisation of the home environment, privacy and confidentiality, promotion of dependence and the effect of technology on the therapeutic relationships of clinicians and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Doolittle et al [16] carried out a retrospective chart review of 597 home visits to adult palliative care patients and identified that 65 percent of these visits could have been conducted by telehealth. Hebert et al [15] conducted a similar study, finding 43 percent of home visits could have received a ‘televisit’ instead. Demiris et al [25,35] criticised this form of evaluating suitability for a telehealth visit as a replacement for in person home visits in two papers, arguing that telehealth is not a suitable substitute for in person visits and that there were ethical implications to consider including the medicalisation of the home environment, privacy and confidentiality, promotion of dependence and the effect of technology on the therapeutic relationships of clinicians and patients.…”
Section: Resultsmentioning
confidence: 99%
“…Video or web conferencing would enable providers external to the interdisciplinary teams to participate in meetings in real time so that decisions could be made quickly and to reduce delays associated with information exchange and coordination. Videoconferencing has been shown to be a practical means of palliative consults [30]. However much of the existing research has been on synchronous one-to-one consults.…”
Section: Resultsmentioning
confidence: 99%
“…Previous such reports describe successful teleconferencing between health care providers in the setting of sparse health care resources and between patients and health care providers when the former live in rural settings. [8][9][10][11][12][13][14] However, none of these interventions includes a patient-initiated electronic encounter, such as that reported here. Along similar lines, ''tele-dermatology'' has been of value in diagnosing rashes with accuracy in a pediatric clinic, in enabling patients with chronic skin conditions to maintain contact with their primary dermatologist with curtailed faceto-face clinic visits, in cutting costs in diagnosing skin cancers, and in reducing the need for a face-to-face dermatology referral by as much as 20% when this type of dermatology consultation was available to primary care providers.…”
Section: Discussionmentioning
confidence: 99%